A crisis of leadership: towards an anti‐sovereign ethics of organisation. (17th December 2012) - Wray‐Bliss, Edward
<x xml:space="preserve">Abstract</x> A common reaction to crises experienced within or brought about by business is to identify a corollary 'crisis of leadership' and to call for better (stronger, more thoughtful or, indeed, more ethical and responsible) leaders. This paper supports the idea that there is a crisis of leadership – but interprets it quite differently. Specifically, I argue that the most ethically debilitating crisis is the fact that we look to leadership to solve organisational ethical ills. There is, I argue, a pressing need to conceptualise a business ethics that is not constrained by the straitjacket of official hierarchy – a need to denaturalise 'leadership' as the normal or rightful locus of ethical regulation and renewal in business organisation. To this end, I explore a Levinasian ethico‐politics of responsibility and proximity as the basis of an alternative, anti‐sovereign, ethics of organisation.